Stress, overeating, and obesity: insights from human studies and preclinical models - Razzoli, Maria (Neurosci Biobehav Rev, 2017)
Eating disorders and obesity have become predominant in human society. Their association to modern lifestyle, encompassing calorie-rich diets, psychological stress, and comorbidity with major diseases are well documented. Unfortunately the biological basis remains elusive and the pharmacological treatment inadequate, in part due to the limited availability of valid animal models. Human research on binge eating disorder (BED) proves a strong link between stress exposure and bingeing: state-levels of stress and negative affect are linked to binge eating in individuals with BED both in laboratory settings and the natural environment. Similarly, classical animal models of BED reveal an association between acute exposure to stressors and binging but they are often associated with unchanged or decreased body weight, thus reflecting a negative energy balance, which is uncommon in humans where most commonly BED is associated with excessive or unstable body weight gain. Recent mouse models of subordination stress induce spontaneous binging and hyperphagia, altogether more closely mimicking the behavioral and metabolic features of human BED. Therefore the translational relevance of subordination stress models could facilitate the identification of the neurobiological basis of BED and obesity-associated disease and inform on the development of innovative therapies.